ANALYSIS OF TIKTOKSHOP CLOSURE POLICY IN SOCIAL COMMERCE AL ISTIHSAN'S PERSPECTIVE - Ainun Elisa; Sudirman Suparmin (Warmadewa Press, 2024)
The policy of closing Social Commerce TikTokShop is an intriguing phenomenon to be analyzed from the perspective of Al Istihsan. This study employs a normative juridical approach with a library research method to elucidate the impact of this policy on legal provisions, particularly Permendag No.31/2023, and the concept of Al Istihsan in Islamic law. Primary legal materials used in this research are relevant legal provisions related to the operation of TikTokShop, particularly Permendag No.31/2023. In the analysis, the author details the violations committed by TikTokShop against these regulations. Additionally, the author utilizes the concept of Al Istihsan as an alternative legal foundation to evaluate the TikTokShop closure policy. Through the library research method, the author outlines research findings from various sources such as books, magazines, journals, articles, and internet sources relevant to the discussed issue. The analysis results indicate that the closure of TikTokShop can be interpreted as an action inconsistent with the concept of Al Istihsan, which emphasizes justice, public interest, and the fair application of law.This research contributes to the understanding of the legal implications of the TikTokShop closure policy and illustrates the relevance of the Al Istihsan concept as an alternative perspective in evaluating legal actions. Therefore, this research is expected to serve as a reference for researchers, legal practitioners, and policymakers in designing more balanced and effective regulations in the current digital era.